On axiomatizations of Boolean algebras - Lisovik, L. P. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We construct some new axiomatic systems for the Boolean algebra. In particular, an axiomatic system for disjunction and logical negation consists of three axioms. We prove the independence of the axiomatic systems proposed.